Workshop Pengenalan Canva sebagai Solusi Desain Praktis untuk Kegiatan Organisasi Karang Taruna desa Kasalib, Banjarnegara - Kirana Kamiliya Zakiyah; Eis Nur Laelasari; Salsabila Nadya Ulya; Andin Isnaeni (JOURNAL SAINS STUDENT RESEARCH, 2026)
The Karang Taruna of Kasalib Village in Banjarnegara needs to use visual media to tell people about what they do.. They have a problem because they do not know how to make their digital content look good. This is because they do not have the skills to design things. So we did a training session to help the Karang Taruna youth learn how to use the Canva application. This will help them make designs for their activities. We taught them the basics of design. Showed them how to use Canva. Then they got to try it out for themselves. We were happy to see that after the training the Karang Taruna youth were 70 percent better at using design features like choosing templates picking the words and adding pictures.Now the Karang Taruna youth can make their own activity posters and other things to post on media. They can do this all by themselves. The Karang Taruna youth are very happy because they can make their village activities look more professional on media. The Karang Taruna youth and the Karang Taruna are very grateful, for this training. The Karang Taruna will keep using the Canva application to make things.